Green synthesis of water splitting electrocatalysts: IrO2 nanocages via Pearson's chemistry. Issue 40 (30th September 2022) - Elmaalouf, Marine; Da Silva, Alexandre; Duran, Silvia; Tard, Cédric; Comesaña-Hermo, Miguel; Gam-Derouich, Sarra; Briois, Valérie; Alloyeau, Damien; Giraud, Marion; Piquemal, Jean-Yves; Peron, Jennifer
Abstract : Hierarchical IrO2 nanocages, easily synthesized in water at room temperature, are extremely active towards the oxygen evolution reaction. The formation mechanism is based on the difference in softness/hardness of the ions involved in the reaction. Abstract : Highly porous iridium oxide structures are particularly well-suited for the preparation of porous catalyst layers needed in proton exchange membrane water electrolyzers. Herein, we report the formation of iridium oxide nanostructured cages, via a water-based process performed at room temperature, using cheap Cu2 O cubes as the template. In this synthetic approach, based on Pearson's hard and soft acid–base theory, the replacement of the Cu2 O core by an iridium shell is permitted by the difference in hardness/softness of cations and anions of the two reactants Cu2 O and IrCl3 . Calcination followed by acid leaching allow the removal of residual copper oxide cores and leave IrO2 hierarchical porous structures with outstanding activity toward the oxygen evolution reaction. Fundamental understanding of the reaction steps and identification of the intermediates are permitted by coupling a set of ex situ and in situ techniques including operando time-resolved X-ray absorption spectroscopy during the synthesis.